Coupling coordination relationship between forestry industry development and the ecological environment: evidence from the Northeast region of China - Zhang, Qi; Bai, DongHui; Kou, ChenHuan; Gao, WenBo (Frontiers in Environmental Science, 2025)
The Chinese economy is entering a new era of high-quality development, and promoting high-quality development has become an inevitable requirement for maintaining healthy economic development and adhering to the laws of economic development. As an essential component of China’s modern economic construction, the high-quality development of the forestry industry will serve as a meaningful way to transform traditional and emerging driving forces and accelerate the construction of ecological civilization. However, as the development of the forestry industry mainly relies on forest resources, the continuous consumption of these resources will inevitably impact the environment, leading to contradictions between the industry’s development and ecological preservation. Therefore, taking the Northeast region as an example, this paper applies the coupling coordination degree model to calculate the coupling coordination relationship between the development of the forestry industry and the ecological environment in Northeast China from 2011 to 2022. This analysis holds important practical significance for promoting coordination between the development of the forestry industry and the ecological environment in the region. The results indicate that, first, the development of the forestry industry and the ecological environment promote, influence, and constrain each other. Second, from 2011 to 2022, there is still a specific gap between the development of the forestry industry and the ecological environment in Northeast China, although both have reached a state of benign coordination. Third, during this period, only Liaoning Province exhibited a relationship between the development of the forestry industry and the ecological environment that included antagonism, adaptation, coupling, and imbalance, while the other two provinces showed no signs of imbalance. Based on the above findings, the Northeast region can promote the coupling coordinated development of the forestry industry and the ecological environment by restructuring the forestry industry transformation model, rationally developing and utilizing forest resources, advocating for clean production projects, and promoting low-carbon economic development.